An investigation and validation of CT scan in detection of spinal epidural adipose tissue. Issue 10 (March 2020) - Chen, Yilei; Hu, Ziang; Li, Zhaozhi; Fan, Shunwu; Zhao, Xing; Song, Lijiang; Wang, Lili
Abstract : Abstract: To investigate the accuracy of computed tomography (CT) in evaluating spinal epidural adipose tissue compared to magnetic resonance imaging (MRI). CT scan images and matched magnetic resonance images of total 368 patients between July 2014 and July 2016 were evaluated. Hounsfield units (HU) of epidural fat (EF), dural sac (DuS), ligamentum flavum, bone of facet joints, and paraspinal muscles were measured for comparison. Anteroposterior diameter of the EF, anteroposterior diameter of the DuS, transverse diameter of the DuS, cross-sectional area of the EF, and cross-sectional area of the DuS were measured at each disc level from L1–2 to L5–S1. Fat tissue showed exclusive negative HU significantly different from all other periphery tissues. Pearson correlation coefficient analyses showed significant positive correlations between CT and MRI measurements; Bland–Altman plots also depicted satisfied agreement. Overgrowth of spinal EF was more commonly found at L2–3 and L3–4 levels in present study, and body weight, age, and gender were significantly associated with amounts of EF both on CT and MRI. The CT scan is a satisfied alternative of MRI for the evaluation of spinal epidural adipose tissue.